Career barriers in the National Hockey League: An inductive thematic analysis of first-hand data from Canadian professional ice-hockey players - Battochio, C. R.; Schinke, J. R.; Stambulova, N. (International Journal of Sport Psychology, 2019)
The objectives of the study were: (a) to examine the Canadian National Hockey League (NHL) players` internal and external barriers associated with the demands at each NHL career stage and status together with across-career barriers, and (b) to feature the Canadian NHL players` barriers in the empirical career model. Five rookies, five veterans, and 13 retirees agreed to participate in conversational interviews before their transcripts underwent an interpretive thematic analysis (Braun & Clarke, 2012). Prospects face draft year pressure and team camp anxiety. Rookies and sophomores deal with insecurity with teammates and roster spot uncertainty. Prime veterans have to manage ruminating over missed chances while seasoned veterans struggled with social connections. Across career stages and statuses, NHL players deal with career threatening injuries and conflicts with head coach. After discussing how these results contribute to the empirical career model of Canadian NHL players and also extend the career transition and maladaptation literatures, delimitations and future directions are proposed for sport psychology researchers.